Prospective comparative evaluation of the European Society of Cardiology (ESC) 1-hour and a 2-hour rapid diagnostic algorithm for myocardial infarction using high-sensitivity troponin-T. Issue 5 (September 2020) - Andruchow, James E.; Boyne, Timothy; Seiden-Long, Isolde; Wang, Dongmei; Vatanpour, Shabnam; Innes, Grant; McRae, Andrew D.
ABSTRACT: Objective: Both 1- and 2-hour rapid diagnostic algorithms using high-sensitivity troponin (hs-cTn) have been validated to diagnose acute myocardial infarction (MI), leaving physicians uncertain which algorithm is preferable. The objective of this study was to prospectively evaluate the diagnostic performance of 1- and 2-hour algorithms in clinical practice in a Canadian emergency department (ED). Methods: ED patients with chest pain had high-sensitivity cardiac troponin-T (hs-cTnT) collected on presentation and 1- and 2-hours later at a single academic centre over a 2-year period. The primary outcome was index MI, and the secondary outcome was 30-day major adverse cardiac events (MACE). All outcomes were adjudicated. Results: We enrolled 608 patients undergoing serial hs-cTnT sampling. Of these, 350 had a valid 1-hour and 550 had a 2-hour hs-cTnT sample. Index MI and 30-day MACE prevalence was ~12% and 14%. Sensitivity of the 1- and 2-hour algorithms was similar for index MI 97.3% (95% CI: 85.8–99.9%) and 100% (95% CI: 91.6–100%) and 30-day MACE: 80.9% (95% CI: 66.7–90.9%) and 83.3% (95% CI: 73.2–90.8%), respectively. Both algorithms accurately identified about 10% of patients as high risk. Conclusions: Both algorithms were able to classify almost two-thirds of patients as low risk, effectively ruling out MI and conferring a low risk of 30-day MACE for this group, while reliably identifying high-risk patients. While both algorithms had equivalent diagnostic performance, the 2-hour algorithm offers several practical advantages, which may make it preferable to implement. Broad implementation of similar algorithms across Canada can expedite patient disposition and lead to resource savings.